Optimization study on a 0.6 kW PMSG for VAWTs and determination of open and short circuit performances by using external circuit method - Çeti̇ncevi̇z, Yücel; Bal, Güngör; Uygun, Durmus (Elsevier BV, 2016)
Abstract As is known, machine design is a time-consuming and complicated process. And consequently, the verification of the designs and machine performances with known optimization methods prior fabrication are becoming more complex and expensive. Relating to this issue, many studies have been achieved to realize optimization and analyze dynamic performance of the designed machines. In this paper, optimization and short/open circuit fault analysis along with transient performance of a designed 0.6 kW radial flux permanent magnet synchronous generator (RFPMSG) for a stand alone wind turbine was studied. The main feature of this study is to use RMxprt dynamic generator model which is linked with the ANSYS Simplorer external circuit simulator. The co-simulation method has been used to analyze the performance of the generator considered for feeding an ohmic load. This method also yields the waveforms of load voltages and load currents for different load and wind speed conditions along with experimental studies.
Keywords: 7. Clean energy